A taxonomic revision of Monstera Adans. (Araceae: Monsteroideae) in Costa Rica - Cedeño Fonseca, Marco Vinicio (2022)
Monstera Adans. (Araceae: Monstereae) is revised for Costa Rica. Thirty-five species are recognised, of which one (M. deliciosa) is introduced. Of them, ten have been only very recently described and Monstera tablasensis M.Cedeño is described as new here. A key to the species is provided, and each is illustrated. Lectotypes, epitypes or neotypes are newly designated for Philodendron pertusum Kunth & C.D.Bouché (the basis of Monstera lennea K.Koch), P. anatomicum J.H.Morsch, M. borsigiana K.Koch, M. dubia (Kunth) Engl. & K.Krause, M. punctulata (Schott) Schott ex Engl., M. tenuis K.Koch, and Marcgravia paradoxa W.Bull ex G.W.Johnson & R.Hogg. Problems with the typification of Monstera adansonii ssp. laniata (Schott) Mayo & I.M.Andrade (Tornelia laniata Schott) are outlined.